Absence, play, and the antidetective story: Shelley Jackson's Half Life. Issue 2 (15th March 2018) - Greer, Amanda
ABSTRACT: Drawing from the tradition of the antidetective story, or the postmodern reversal of the classical detective genre, Shelley Jackson's Half Life provides a Derridean critique of binary oppositions. This essay will illustrate the ways Jackson borrows heavily from both detective stories and Derrida's theories of the repressed absence at the heart of the sign in order to propose a (non)resolution to binary thinking. Half Life frames itself as a tale of detection, but absence lies at both the heart of the mystery and Jackson's narrative technique. Rather than collapsing around its central absence into an almost clichéd postmodern hopelessness, Half Life urges its readers to solve its central mystery by provoking the expectation of a solution. By refusing to provide that resolution, however, Jackson both defies the idea of a definitive solution and demonstrates that absence can be both fundamental and engaging.